Changes in the Intra-household Roles in Agriculture among Tiv Farming households in Nigeria - OLAOLU MICHAEL OLATUNJI; Dooshima P IVANDE; Edwin M Igbokwe (Journal of Agricultural Extension, 2015)
The division of labour in traditional settings assigns specific roles to family members according to their age, gender and status. This study therefore, assessed the changes in the household roles in agriculture among the Tiv farmers during the colonial and post colonial period. Data was collected with the aid of interview schedule that was administered on 315 household heads who are aged 50years and above. The analytical tools used included descriptive statistics such as means and percentages and the student’s t-test. The findings revealed remarkable changes in the intra-household labour roles as men were more involved in the application of fertilizer (433% change) and product marketing (311% change) which were earlier women roles. The t-test on changes in the social organisation and capital in agriculture shows a significant change (P<0.05) in communal cooperation in the colonial and post colonial period. Due to the fact that men are now also involved in the household activities which had earlier been known as female roles; it is recommended that extension agents should target both male and female clientele on home economics technologies